2008
DOI: 10.2459/jcm.0b013e3282f25e9f
|View full text |Cite
|
Sign up to set email alerts
|

Double rhythm in double heart

Abstract: We describe the case of a patient with heterotopic transplantation, sinus rhythm originating from the donor heart, ventricular fibrillation of the native heart and right severe decompensation. The double rhythm was easily detected with a surface ECG and the transthoracic echocardiogram, both performed in the left conventional and in the right modified mode. The patient was successfully treated with direct current shock with quick restoration of native heart synchronization and clinical relief of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There is a paucity of reports of native heart ventricular fibrillation in heterotopic heart transplant recipients with widely varying degrees of haemodynamic compromise and management strategies [1][2][3][4]. Our case adds to the literature on the roles of synchronized DC cardioversion as an effective immediate therapy and amiodarone as a secondary preventative measure for a rare but serious problem.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 54%
“…There is a paucity of reports of native heart ventricular fibrillation in heterotopic heart transplant recipients with widely varying degrees of haemodynamic compromise and management strategies [1][2][3][4]. Our case adds to the literature on the roles of synchronized DC cardioversion as an effective immediate therapy and amiodarone as a secondary preventative measure for a rare but serious problem.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 54%
“…Separation of the two hearts in their rhythm may cause double rhythm in double heart. Potenza et al reported ventricular fibrillation of the native heart and sinus rhythm of the donor heart in a patient with heterotopic transplantation [2]. HHT was a more useful technique before improvement in immunosuppression regimes and mechanical circulatory support, as it helped to maintain circulation in the cases of acute graft failure [3].…”
Section: Discussionmentioning
confidence: 99%